#TRANSFORMANDOSUOREMOURO: BEHIND A BALL HAS A PHILOSOPHY (Fiep Bulletin - online, 2015)
This article aims to demonstrate the viability of Professional Physical Education offer their contribution of multidisciplinary manner, using the technology available today on an ally to overcome difficulties, giving opportunities to students to seek new paths and through guided practice of Physical Education, contextualize everyday and will become a citizen through the mediation of conflicts, using appropriate language, aimed at changing behavior. The experience is with the basketball teams of the College of PMPE, who managed to inspire the teachings of the book Turning sweat into gold, the renowned Brazilian coach selected volibolRezende, and internalizing their ideas, succeeded in 365 (three hundred and sixty five) days, turning a simple basketball team as one of the references in Pernambuco, but even more was the formation of character and attitude change implemented.
Keywords: Interaction; Physical Education; Network.